A physiological sensor network supported by an inductive communication link - Hoskins, Seth (Kansas State University, 2011)
The continuous and autonomous real-time monitoring of cattle state of health can provide major benefits for the U.S. livestock industry and lead to a higher quality beef product. Complete real-time monitoring could not only lead to earlier detection of disease in individual animals and reduce the spread of disease to a larger herd, but it could ultimately reduce the cost and frequency of on-site veterinary consultations. This thesis details a wearable device that is mounted on cattle to collect data from a network of internal and external sensors. In addition to the basic data collection, this thesis will describe the infrastructure to communicate these data sets to a central database for permanent storage and future analysis. Physiological, ambient environment, and physical activity data are acquired by the various sensors to give a good indication of the state of health of an animal wearing the device. The communication of data from internal sensors to an external wearable receiver is of particular interest since tissue is not an ideal medium for radio-frequency data transmission. Past research has attempted to use such links with little success due to large signal attenuation at high frequencies and a package that becomes much too large to be usable at low frequencies. As a result, a wireless communications method employing magnetic inductance at relatively low frequencies over short distances is described here.
Keywords: Wireless communications; Biomedical telemetry; Biomedical Engineering (0541); Communication (0459); Electromagnetics (0607)